2022
DOI: 10.1108/jbim-09-2021-0441
|View full text |Cite
|
Sign up to set email alerts
|

Examining the functionality of digital platform capability in driving B2B firm performance: evidence from emerging market

Abstract: Purpose This study aims to explore the influence mechanism of digital platform capability on firm performance in the business-to-business (B2B) context. This study draws on the core competence theory and the resource-based view and includes resource identification, resource allocation and intrapreneurship into the research framework. Design/methodology/approach Data were collected from 167 B2B firms with survey questionnaires in central, eastern and southeastern coastal areas of China. The firms were mainly … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
18
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 67 publications
0
18
0
Order By: Relevance
“…Cause-related B2B marketing programs create a specific type of B2B network: sponsoring organisations and NPOs. A detailed understanding of the combination of factors driving adoption would enable both entities in the cause-related B2B marketing program to develop B2B digital platform capabilities as core competencies, furthering their market performance (Wang et al , 2017; Liu et al , 2022). The study findings are in line with existing studies that a better understanding of factors inhibiting the adoption of Digital B2B platforms in B2B networks (business associations, chambers of commerce and employer’s unions) can enable development of better capabilities and satisfaction of the needs of the business networks (Cenamor et al , 2019; Peruchi et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Cause-related B2B marketing programs create a specific type of B2B network: sponsoring organisations and NPOs. A detailed understanding of the combination of factors driving adoption would enable both entities in the cause-related B2B marketing program to develop B2B digital platform capabilities as core competencies, furthering their market performance (Wang et al , 2017; Liu et al , 2022). The study findings are in line with existing studies that a better understanding of factors inhibiting the adoption of Digital B2B platforms in B2B networks (business associations, chambers of commerce and employer’s unions) can enable development of better capabilities and satisfaction of the needs of the business networks (Cenamor et al , 2019; Peruchi et al , 2022).…”
Section: Discussionmentioning
confidence: 99%
“…In a study Cenamor et al (2019) suggested that Digital B2B platforms enhance entrepreneurial SMEs’ market competitiveness by creating resources and capabilities due to the network effect. Investments in developing Digital B2B platform capabilities enable a firm to gain a competitive advantage by better-controlling business processes and systems (Mai and Liao, 2021; Liu et al , 2022). Digital B2B platform capabilities are inculcated at the adoption stage of these digital platforms.…”
Section: Literature Reviewmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, we define DPC as the capability to deploy information and communication technology-based resources and integrate other internal and external resources (Cenamor et al , 2019). To cope with the turbulent environment, many firms realize their business value by developing digital platform capabilities (Liu et al , 2022). Despite the potential value of DPC, we lack key empirical evidence in theory to prove the benefits that it brings to the resilience of service firms for the following reasons.…”
Section: Introductionmentioning
confidence: 99%